2017
DOI: 10.3141/2648-06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Train and Station Types on Perceived Quality of Rail Service

Abstract: This paper aims to highlight the impact of train and station types in the evaluation of service quality, whilst taking account of a range of relevant trip and socio-demographic factors. It applies a partial constrained proportional odds model (an extension of ordered logit model) to data extracted from the 32 nd wave of the National Rail Passenger Survey (NRPS) held in spring 2015, which comprises around 30,000 trip-level observations of passenger satisfaction of rail services across Great Britain.The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Comfort in terms of station facilities is reported to have less impact on perceived service quality in regional public transport [68], although the results of our review suggest that this conclusion might require modification. On-board comfort is clearly important for medium and long regional trips, but there are indications that station facilities are more important for short regional trips.…”
Section: The Influence Of Trip Lengthcontrasting
confidence: 57%
See 2 more Smart Citations
“…Comfort in terms of station facilities is reported to have less impact on perceived service quality in regional public transport [68], although the results of our review suggest that this conclusion might require modification. On-board comfort is clearly important for medium and long regional trips, but there are indications that station facilities are more important for short regional trips.…”
Section: The Influence Of Trip Lengthcontrasting
confidence: 57%
“…Still, punctuality is the most common measure of reliability, and it is shown that delays significantly impact the level of passenger satisfaction [68]. Higher probability of delays also decreases the probability of choosing public transport modes [39,43].…”
Section: Time 441 Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is interesting to note, that each group of users reported higher average satisfaction with on-time performance than communication of delays. Delays incurred by passengers have negative effects on overall satisfaction levels reported by customers (41). However, policies aimed at minimizing frustration and confusion in the event of a delay are important and cost-effective strategies that will likely lead to a higher perceived service quality and should not be over-looked by transit agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have investigated either access mode ( 6 9 ) or station choice ( 10 , 11 ). However, studying the combination of these choice dimensions could shed light on important trade-offs that cannot be captured otherwise.…”
mentioning
confidence: 99%